Best Practice for Financial Models of PPP Projects. (2015) - Kurniawan, Fredy; Mudjanarko, Sri Wiwoho; Ogunlana, Stephen
Abstract: Public-private partnership (PPP) project's arrangement involves many participants with complex transactions and diverse interests at 5 different project stages. Especially in the project financing perspective, this arrangement creates the entire project evaluation process prone to take an extensive period before reaching financial closure. The importance of utilizing financial model as a tool for project evaluation and negotiation is highlighted in this study. 26 input assumptions and 16 output variables have been identified through comparison study of three PPP financial models, and their significances were verified based on pilot studies in India and the UK and expert opinion solicited worldwide through a structured questionnaire survey. SPSS program was used to evaluate the survey responses. The best practice PPP financial model was identified quantitatively by the agreement of four groups of stakeholders (i.e. sponsors, authorities, lenders, and consultants) upon the most preferred financial input and output indicators.